Text message feedback to support mindfulness practice in people with depressive symptoms: a pilot randomized controlled trial - Kraft, Susanne; Bauer, Stephanie (JMIR mhealth and uhealth)
Background: It has been shown that mindfulness practice can be helpful in preventing relapse from depression. However, practicing mindfulness regularly at home is often a challenge for people with depression. Mobile phone text messaging (short message service, SMS) may be a feasible approach to assist regular mindfulness home practice. Objective: The aim of this study was to evaluate the feasibility of text message-based feedback to support mindfulness practice in people with depressive symptoms after inpatient psychiatric treatment. Methods: Participants received a manualized group introduction to three mindfulness exercises during inpatient treatment and were randomized at hospital discharge. All participants were asked to practice the exercises daily during the 4-month follow-up period. Only participants allocated to the intervention group received reinforcing feedback via mobile phone text messages after reporting their mindfulness practice via text message. Participation rates and satisfaction with the interventions were evaluated, and effects on relevant outcomes were explored. Results: Of the 176 eligible inpatients invited to participate, 65.9% (116/176) attended the introductory mindfulness group at least once, 33.0% (58/176) were willing to participate in the study, and 41 were randomized. The majority 85% (35/41) of these participants completed the study. Among the participants allocated to the intervention group (n=21), 81% (17/21) used the text message support at least once. The average number of text messages sent during the intervention period was 14 (SD 21, range 0-91). Satisfaction rates were high. Preliminary analyses of the effects of the intervention yielded mixed results. Conclusions: Findings indicate that text messaging following inpatient treatment is feasible for some, but not for all people with depressive symptoms. Modest use of the text messaging intervention and its mixed effects imply that dose and ingredients of the intervention should be increased for this group of patients in a future full-size RCT. Such a larger study should also include a process evaluation to investigate moderators of the effect of mindfulness practice and text message feedback on clinical outcome. Trial Registration: International Standard Randomized Controlled Trial Number (ISRCTN): 58808893; http://www.controlled-trials.com/ISRCTN58808893 (Archived by Webcite at http://www.webcitation.org/6pmrDRnGt) [JMIR Mhealth Uhealth 2017;5(5):e59]
Gesehen am 09.11.2018